Information Technology Governance Research in the Digital Era: A Scopus-Based Bibliometric Analysis - Loso Judijanto; Hanifah Nurul Muthmainah; Joni Wilson Sitopu (The Eastasouth Journal of Information System and Computer Science, 2026)
This study aims to map and analyze the global research landscape of information technology (IT) governance in the digital era through a bibliometric approach. Data were retrieved from the Scopus database and analyzed using VOSviewer software to examine co-authorship patterns, institutional collaborations, country contributions, keyword co-occurrence structures, and citation impact. The co-authorship network reveals that this segment of the literature is dominated by a single, tightly interconnected research team rather than a broad community of independent contributors, while institutional collaboration remains sparse and is bridged only by a public-administration-affiliated unit connecting a geospatial land-governance research community with a cross-border, financial-technology-oriented data-governance community. At the country level, China, the United States, the United Kingdom, India, and Indonesia emerge as the principal hubs of international collaboration, supported by extensive participation from Europe, the Middle East, and Southeast Asia, indicating that IT governance research constitutes a genuinely global, multipolar undertaking. The keyword co-occurrence analysis shows that the field is organized around four interconnected clusters covering cybersecurity and blockchain-based governance, artificial intelligence and digital transformation, big data-driven decision-making, and e-government and ICT-based public governance, with digital governance and information management forming the field's conceptual core. The citation analysis further shows that the field's intellectual foundation is anchored in the digital-era governance model and its subsequent extension toward artificial intelligence, alongside diverse contributions from e-government adoption, geospatial data integration, and data-driven policymaking research. Taken together, these findings indicate that IT governance research has developed into a rapidly expanding, technology-driven field, with growing convergence toward artificial intelligence, cybersecurity, and data governance as its emerging frontiers.